Automatic Fish Feeder on Unmanned Surface Vehicle with Automatic Control and Navigation - FARIED IZZANTAMA NUGRAHA HARSWA; Angga Rusdinar; Rifqy Miftahul Hidayat; Fiky Yosep Suratman (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2022)
Fish farming is common in Indonesia. The farmers usually use ponds with a large size for cultivation which have constraints on feeding due to their size. An automatic feed system with An Unmanned Surface Vehicle (USV) can be the solution to overcome this problem. The USV moves to the predetermined position and direction using GPS and compass. When it has arrived at that point this USV feeds the fishes according to the predetermined amount. In this study, the Pixhawk is used to control the USV to accomplish the given mission. It uses mission planner software for determination of the waypoint points, the calibration of components, and the control of PID. The Pixhawk also serves as a ground control station (GCS) for monitoring the motion and position of the USV using radio communication of 433MHz telemetry connected to the GCS and computer. The fish feeding system uses a load cell sensor to measure the weight of the feed to be thrown and two servo motors as a feed production system. Both sensor and servo motors are controlled by an Arduino UNO. The feed tank has a maximum capacity of 7.5 liters with 0.41 cm per kilogram buoyant force of the USV. The test was carried out on a pool of 10 × 10 m by placing 4 Waypoints. The USV has an average speed of 0.65 m/s and reaches a total distance of 55.5 m in 88 seconds. Before releasing to the pond, the feed weight is measured using a load cell sensor which has an accuracy of 98.99%. The difference between the set point and the feed released by the USV is very close, where the average error value is about 4.98%. The error value becomes smaller when more weight is set.